Effects of the Presence of Distributed Generation on Protection and Operation of Smart Grid Implemented in Iran; Challenges and Solutions - Hossein Shahinzadeh (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Installation of distributed generation (DG) in distribution networks, in addition to the benefits, will also cause drawback and disadvantages which can bring difficulties for grid operator. Thus, prior to installation of DGs, it is essential to have deeply studied about their installation in the network and it is needed to make some changes in traditional network. Implementation of smart grids is one of the main requirements for the proper and efficient operation of DGs. In Iran, Smart grid is also being implemented, but with the development of DGs, electricity distribution companies face new problems related to DGs every day. One of the most important problems is about effects of the DGs on proper operation of protective equipment which is mainly due to radial distribution network. That is because in Iran, despite the implementation of smart grids, distribution networks are designed and implemented radially and airlines with isolated neutral point is usually used in the distribution network. So, in this article, the impacts of distributed generation resources on distribution networks in Iran and Protection and operational problems which may cause in this area are studied and solutions to these problems are provided.